Erratum to: “Marine sponges as a drug treasure” [Biomol.Ther. 24 (2016) 347?362] - Anjum, Komal; Abbas, Syed Qamar; Shah, Sayed Asmat Ali; Akhter, Najeeb; Batool, Sundas; Hassan, Syed Shams ul (Biomolecules & Therapeutics, 2016)
Komal Anjum, Syed Qamar Abbas, SayedAsmat Ali Shah, Najeeb Akhter, Sundas Batool, and Syed Shams ul Hassan. Biomolecules & Therapeutics 2016;24:559. https://doi.org/10.4062/biomolther.2016.559
Gesehen am 18.08.2020